2015
DOI: 10.4172/2327-5073.1000186
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Antibiotic Susceptibility Patterns of Shigella and Salmonella among Under 5 Children with Acute Diarrhoea: A Cross-Sectional Study at Selected Public Health Facilities in Addis Ababa, Ethiopia

Abstract: Background: Diarrhoeal illness remains one of the leading causes of morbidity and mortality among children<5 years of age worldwide. In Ethiopia, about 230,000 deaths estimated to occur. Shigella and Salmonella are major causes of gastroenteritis in children and is associated with high resistance levels. Thus, the aims of this study was to isolate and determine susceptibility patterns of Shigella and Salmonella, isolated from under five children with diarrhoea attending at some selected health facilities in Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
28
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 21 publications
27
28
9
Order By: Relevance
“…There is high resistance of Shigella to commonly used antibiotic agents Ampicillin, Amoxicillin, TrimethoprimSulphamethoxazole, and Chloramphenicol, a finding corroborated with previous reports in Ethiopia [8], [9], [21], [22]. This finding is similar with studies done in different parts of Ethiopia.…”
Section: Discussionsupporting
confidence: 91%
“…There is high resistance of Shigella to commonly used antibiotic agents Ampicillin, Amoxicillin, TrimethoprimSulphamethoxazole, and Chloramphenicol, a finding corroborated with previous reports in Ethiopia [8], [9], [21], [22]. This finding is similar with studies done in different parts of Ethiopia.…”
Section: Discussionsupporting
confidence: 91%
“…The overall prevalence of Shigella and Salmonella isolated in this study was 8.0% [4.6-11.4%] which is lower than compared with studies conducted in Tanzania A single S. Typhi 0.4% 95% CI [0-1.1%] was isolated in this study which is in line with the ndings reported from the same country in Addis Ababa, 0% (31), 1.1% (43), in contrast to our nding higher rates was reported from Sudan 4.0% (40), China 4.3% (27), Addis Ababa, Ethiopia 3.95% (26), Kenya 3.4% (46), Turkey 3% (47), Gondar 1.6% (48), and Hawassa 1.5% (24). This difference might be due to sampling size, weather condition and study subjects age differences.…”
Section: Discussionsupporting
confidence: 86%
“…Salmonella and particularly Shigella species are increasingly acquiring resistance to commonly used antibiotics, most importantly to third-generation cephalosporins (3GC), as the main drug of choice for the treatment of Salmonella and Shigella infections, through the production of extended-spectrum β-lactamases (ESBLs) (6)(7)(8)(9). Data on local antibiotic resistance patterns are essential to have an empiric antibiotic treatment guideline adapted to the Copyright © 2018, Author(s).…”
Section: Introductionmentioning
confidence: 99%